2020
DOI: 10.1111/bjso.12424
|View full text |Cite
|
Sign up to set email alerts
|

Embrace the leadership challenge: The role of Gay men’s internalized sexual stigma on the evaluation of others’ leadership and one’s own

Abstract: Grounded in the framework of the gay glass ceiling, the current research investigated the effect of gay men's internalized sexual stigma (ISS) on both the perceived effectiveness of other gay men's leadership and on their self-perceived leadership effectiveness and their intention to apply to a leadership position. In three studies (N = 402), we manipulated either the leader's sexual orientation (SO) (study 1), or his adherence to traditional gender roles (TGR) (study 2), or participants' fictitious masculinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…Before completing the BSRI, participants read on a screen that the test returns a total score from 0 to 50, whereby zero corresponds to an extremely feminine personality and 50 corresponds to an extremely masculine personality. This procedure replicated that which was employed in other studies (Glick et al, 2007; Hunt et al, 2016; Salvati et al, 2016; 2020).…”
Section: Methodsmentioning
confidence: 79%
See 1 more Smart Citation
“…Before completing the BSRI, participants read on a screen that the test returns a total score from 0 to 50, whereby zero corresponds to an extremely feminine personality and 50 corresponds to an extremely masculine personality. This procedure replicated that which was employed in other studies (Glick et al, 2007; Hunt et al, 2016; Salvati et al, 2016; 2020).…”
Section: Methodsmentioning
confidence: 79%
“…The present research investigates implicit negative associations with stereotypically masculine and stereotypically feminine gay men in a sample of both heterosexual and gay/bisexual (GB) men, by manipulating their self-perceived masculinity through fictitious feedback to the Bem Sex-Role Inventory (BSRI; Bem, 1974; Glick et al, 2007; Salvati et al, 2020). We collected participants’ adherence to traditional masculinity, their norms of traditional masculinity ideology, their sexual prejudice (in heterosexual male participants), and their internalized sexual stigma (in gay male participants).…”
Section: The Present Studies and Hypothesesmentioning
confidence: 99%
“…Research on recruitment for leadership positions has found either that lesbian women face a higher degree of discrimination in recruitment than gay men do (Fasoli and Hegarty, 2019), that lesbian women and gay men face equal amounts of discrimination (Fasoli et al, 2017), or that lesbian women and gay men are as equally likely to be hired as their heterosexual counterparts (Niedlich and Steffens, 2015). Moreover, gay men who display gender non-conformity have been evaluated less positively as leaders than gender conforming gay men (de Cristofaro et al, 2020;Salvati et al, 2021). We have found no similar research on the effect on leadership potential of gender conformity of lesbian women.…”
Section: Suggestions For Future Researchmentioning
confidence: 99%
“…Contrasting these findings, there is also evidence that gay men are not discriminated against (Van Hoye & Lievens, 2003), and they appeared similar (in agency and hireability) for masculine‐typed jobs when compared with heterosexual men (Niedlich & Steffens, 2015). Regardless of their sexual orientation, feminine leaders were rated as less effective than masculine leaders (De Cristofaro et al, 2020) (also see Salvati et al, 2021), and applicants with gay or lesbian sounding voices were discriminated against as compared to applicants with voices sounding heterosexual (Fasoli et al, 2017; also see Fasoli & Hegarty, 2020).…”
Section: Introductionmentioning
confidence: 99%